Co-sensitization of Dithiafulvenyl-Phenothiazine Based Organic Dyes with N719 for Efficient Dye-Sensitized Solar Cells. (1st September 2016) - Luo, Junsheng; Wan, Zhongquan; Jia, Chunyang; Wang, Yan; Wu, Xiaochun; Yao, Xiaojun
Graphical abstract: Highlights: Two novel dithiafulvenyl-phenothiazine (DTF-PTZ) based organic dyes were synthesized. N719 and DTF-PTZ dyes were used for the fabrication of co-sensitized DSSCs. The PCEs of DSSCs based on co-sensitization were higher than individual dye. DSSC based on co-sensitization ofN719 andPTZ-2 showed the highest PCE of 8.12%. The highest PCE of co-sensitization DSSC was 16.50% higher thanN719 based device. Abstract: The introduction of additional electron donor and elongation of π-conjugated bridge represents a feasible strategy to enhance light harvesting in both breadth and intensity of donor-(π conjugated spacer)-acceptor (D-π-A) dyes suitable for dye-sensitized solar cells (DSSCs). Here, two novel metal-free organic dyes, in which dithiafulvenyl unit was introduced into phenothiazine donor as an additional electron donor, cyanoacrylic acid as the electron acceptor, and without (PTZ-2 ) or with (PTZ-3 ) a benzene as the π-linker between phenothiazine donor and cyanoacrylic acid electron-withdrawing group, were synthesized by modifying the simple D-π-A dye (PTZ-1 ) and successfully utilized in DSSCs. Their photophysical, electrochemical, photovoltaic properties and theoretical calculations were further investigated. Relative to the reference dyePTZ-1, the power conversion efficiencies (PCEs) increased significantly from 4.04% to 5.81% (PTZ-2 ) and 5.22% (PTZ-3 ), which came mainly from the enhancement of short-circuit current ( J sc ) due to the broader molecular absorption spectra and higher molar extinction coefficients. What's more, it is worth noting that the dyes ofPTZ-2 andPTZ-3 have strong absorption, which can compensate for that ofN719 in the low wavelength region, especially in the region of ∼300–500 nm. Therefore, a co-sensitization approach has been used for achieving enhanced performances in DSSCs whereinN719 was co-sensitized withPTZ-2 andPTZ-3, respectively. Consequently, the co-sensitized DSSC (PTZ–2 + N719 ) gave the highest efficiency of 8.12%, exhibiting an improvement of 16.50% compared to the device sensitized withN719 alone (PCE = 6.97%) under the same conditions.